2017
DOI: 10.5858/arpa.2016-0629-oa
|View full text |Cite
|
Sign up to set email alerts
|

Duplicate Type and Screen Testing: Waste in the Clinical Laboratory

Abstract: - Our study demonstrates that inappropriate TS ordering is costly, both financially and clinically. By evaluating the percentage of inappropriate TS tests by clinical services, we have identified services that may benefit from additional education and technologic intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The range of HHb concentrations is chosen to investigate sensitivity of the MIP in diluted blood samples, which would enable decreasing the sample volume up to a factor 1000, thus strongly reducing medical waste in clinical applications. [76,[103][104][105][106][107] Figure 3b shows the calibration curve of the MIP-and NIP-coated PSiO 2 scaffolds. Two linear regions are evident for the MIP-based sensor, namely, a higher-sensitivity region between 0.1 and 1 mg mL −1 and a lower-sensitivity region between 1 and 8 mg mL −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The range of HHb concentrations is chosen to investigate sensitivity of the MIP in diluted blood samples, which would enable decreasing the sample volume up to a factor 1000, thus strongly reducing medical waste in clinical applications. [76,[103][104][105][106][107] Figure 3b shows the calibration curve of the MIP-and NIP-coated PSiO 2 scaffolds. Two linear regions are evident for the MIP-based sensor, namely, a higher-sensitivity region between 0.1 and 1 mg mL −1 and a lower-sensitivity region between 1 and 8 mg mL −1 .…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that transplant physicians may have a practice habit of screening for fungal infections among transplant patients that they extend to nontransplant patients as a possible explanation for why they were more likely to order avoidable tests in these lower-risk patients. Inappropriate test ordering by specific clinical services has been reported previously; for example, a single-center retrospective study from Vanderbilt University Medical Center showed that duplicate type and screen tests for nontransplant patients were more common among adult services than pediatric services [ 16 ]. Additionally, several departments, especially where they care for transplant recipients, used NCBFAs in the routine order sets on admission or when working up for fever or increased inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%